Head impact exposure comparison between male and female amateur rugby league participants measured with an instrumented patch - DA, King; PA, Hume; C, Cummins; T, Clark; C, Gissane; M, Hecimovich (Journal of Sports Medicine and Therapy, 2019)
Background: Epidemiological studies report that females experience greater rates of concussion when compared with males. Biomechanical factors may result in greater post-impact head velocities and accelerations for a given force for females when compared with males. Purpose: To quantify the magnitude, frequency, duration and distribution of impacts to the head and body in rugby league match activities for females versus males. Design: Prospective descriptive epidemiological study. Methods: 21 female and 35 male amateur rugby league players wore wireless impact measuring devices (X2Biosystems; xPatch) behind their right ear over the mastoid process during match participation across a single season. All impact data were collected and downloaded for further analysis. Results: Male amateur rugby league players experienced more head impacts than female amateur rugby league players (470 ±208 vs. 184 ±18; t(12)=-3.7; p=0.0028; d=1.94) per-match over the duration of the study. Male amateur rugby league players recorded a higher median resultant Peak Linear Acceleration (PLA(g)) (15.4 vs. 14.6 g; F(824,834)=51.6; p<0.0001; t(1658)=-3.3; p=0.0012; d=0.10) but a lower median resultant Peak Rotational Acceleration (PRA(rad/s2) (2,802.3 vs. 2,886.3 rad/s2; F(831,827)=3.1; p<0.0001; t(1658)=5.7; p<0.0001; d=0.13) when compared with female amateur rugby league players Conclusion: Females recorded lower median values for PLA(g) and Head Impact Telemetry severity profile (HITSP) for all positional groups but had a higher PRA(rad/s2) for Hit-up Forwards (HUF) and Outside Backs (OSB’s) when compared with male HUF and OSB’s. Females also recorded more impacts to the side of the head (48% vs. 42%) and had a higher 95th percentile resultant PRA(rad/s2) (12,015 vs. 9,523 rad/s2) to the top of the head when compared with male rugby league players.